Wagnerian Aesthetics as Expressionist Foundations of Alban Berg’s Music and the Russian Silver Age - Ljubibrati´c, Vanja (Danish Yearbook of Musicology, 2018)
Richard Wagner, Alban Berg, and intellectuals of the Russian Silver Age are compared and contrasted in ways that draw up specific examples of how Wagner’s theories and aesthetics were integral in forming the morals and perceptions of Berg and the Russians, both for their personal truths as well as for that of their art. The concept of Expressionism is the cement that fuses all these ideals and individuals across the aesthetic landscape between the mid-nineteenth century and the early twentieth century. Wagner is shown to be a forerunner of Expressionism due to his early ideas about the role of culture in society. The article also reveals that his later, more important preoccupation with inner states of consciousness and being were recognized and valued by Expressionists from a variety of art forms. The important distinction being, however, that recognition of these traits within Wagner’s output was only the beginning. Indeed, both Berg and the Russians would appropriate Wagnerian ideals for their own purposes, thereby simultaneously evolving and morphing the foundation that Wagner established for them in order to enact the changes they felt to be natural and necessary.